Emerging Role of Epigenetics in Explaining Relationship of Periodontitis and Cardiovascular Diseases - Syed Ameer Hamza; Saba Asif; Zohaib Khurshid; Muhammad Sohail Zafar; Syed Akhtar Hussain Bokhari (Diseases, 2021)
Cardiovascular diseases such as ischemic heart diseases or stroke are among the leading cause of deaths globally, and evidence suggests that these diseases are modulated by a multifactorial and complex interplay of genetic, environmental, and lifestyle factors. Genetic predisposition and chronic exposure to modifiable risk factors have been explored to be involved in the pathophysiology of CVD. Environmental factors contribute to an individual’s propensity to develop major cardiovascular risk factors through epigenetic modifications of DNA and histones via miRNA regulation of protein translation that are types of epigenetic mechanisms and participate in disease development. Periodontal disease (PD) is one of the most common oral diseases in humans that is characterized by low-grade inflammation and has been shown to increase the risk of CVDs. Risk factors involved in PD and CVD are determined both genetically and behaviorally. Periodontal diseases such as chronic inflammation promote DNA methylation. Epigenetic modifications involved in the initiation and progression of atherosclerosis play an essential role in plaque development and vulnerability. Epigenetics has opened a new world to understand and manage human diseases, including CVDs and periodontal diseases. Genetic medicine has started a new era of epigenetics to overcome human diseases with various new methodology. Epigenetic profiling may aid in better diagnosis and stratification of patients showing potential predisposed states for disease. A better understanding of the exact regulatory mechanisms of epigenetic pathways driving inflammation is slowly emerging and will aid in developing novel tools for the treatment of disease.